The awareness of ICT implementation for materials management in construction projects - Kasim, Narimah; Peniel Ang, Soon Ern (Interscience Journals, 2010)
Construction materials usually constitute a major portion of the total cost in a building construction project. Despite the potential benefit of ICT, convincing construction organisations to embrace its use and implementation has proved a difficult task. This research seeks to identify the implementation of ICT in construction materials management processes and to investigate on the acceptance of contractors for ICT transformation to the materials management in construction projects. In relation to that, current constraints that are found hindering the acceptance of ICT in materials management processes are also identified. A triangulation research approach which consists of standard derived questionnaires, semi structured interviews with class A contractors and review of previous research were conducted. The findings from this research reveal that the implementation of ICT in the materials management for construction projects in Malaysia is at early stage. Microsoft Excel Spreadsheet and handheld devices are found to be the common ICT tools adopted in the materials management processes. Meanwhile, there is only an average level of acceptance towards the transformation of ICT implementation in the construction materials management. The main barrier is found to be the cost involvement at the initial stage or overall implementation of ICT in the materials management processes. Finally, it can be concluded that there is a lack of awareness towards the ICT implementation of materials management in the construction projects.